Análisis de los factores que inciden en la morosidad de los tarjetahabientes en la ciudad de Guayaquil, provincia del Guayas, período lectivo del 2015 al 2017.- 2017 - López Paredes, Priscilla Carolina (2020)
Credit cards are currently one of the most accepted forms of payment worldwide and the proper administration of these will prevent cardholders from falling into arrears of the obligation. The general objective of the research work focused on determining the incidence of the factors of the use of credit cards in the delinquency of the cardholders of the city of Guayaquil. The applied research methodology had a quantitative and qualitative approach of descriptive scope, non-experimental design and cross-section. The tool for data collection was the analysis of information from government entities, a focus group and interviews……….